Bidirectional Nature of Work Family Conflict: Family Interfering with Work Conflict Among Athletic Trainers in the Collegiate Setting - Stephanie Singe; Milana Adaspour; Alexandrya Cairns; William Pitney (Bowling Green State University, 2024)
Introduction: Work-family conflict is bidirectional, yet research has largely only investigated the extent to which work interferes with family conflict (WIFC) and not whether family interferes with work conflict (FIWC). Objective: Investigate FIWC among collegiate athletic trainers. Specifically, we were focused on relationships between gender, marital status, employment status of the athletic trainer's spouse, and number of children. Methods: Data were collected via a cross-sectional, online survey (Qualtrics). Descriptive statistics were calculated for demographic information; Mann Whitney U analyses were utilized to discover differences between gender, marital status, employment status of spouse, and number of children. Results: 984 (605 women, 370 men, 9 other) collegiate athletic trainers. Cronbach's alpha resulted in acceptable reliability of the WIFC (.92), the FIWC (.86), and the total WFC scale (.84). Women reported significantly higher FIWC scores than men (U=93539.5, pConclusions: Women athletic trainers reported higher levels of FIWC than men. We found both single and married with children athletic trainers report high levels of FIWC, suggesting both groups experience the challenges of family demands. Interestingly, children did not impact experiences of FIWC.